Pengembangan Media Pembelajaran Lemari Pintar Tema Lingkungan Sahabat Kita Untuk Siswa Kelas V SD/MI - Oktianingsih Ari Rusmianto; M. Iqbal Baihaqi; Minto Santoso (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2023)
The inadequate condition of the infrastructure and the lack of teacher creativity in making learning media becomes an obstacle for students so that it is difficult to understand the subject matter. This study aims to (1) determine the development of smart cupboard media for fifth grade students of SD / MI (2) to determine student responses to instructional simulations of smart wardrobe learning media for class V SD / MI students (3) to determine the steps for using smart wardrobe media for grade V SD / MI students. This type of research uses the RnD approach, by adopting the research steps of the Borg and Gall model, only up to seven stages. The instruments used in this study included questionnaires, interview guides, and observation sheets. The trials were carried out internally and externally. Internally to find out the feasibility of the product, while internally to find out the student's response to the media and the steps for using smart wardrobe learning media using a pre-experimental design research design type one-shoot case study. The results of the eligibility of the media expert validator are 84%, material experts 90% and linguists 82%. So the smart wardrobe learning media is suitable for learning. The results of the questionnaire student responses to the media had an average of 89%. The steps for the smart wardrobe learning media consist of 8 steps.